Effect of potato and apple peels on the growth of Beta vulgaris (Journal of the College of Basic Education, 2023)
An experiment was conducted to study the effect of mixing potato peelings, apple peels, and a mixture of potato peelings and apple peels with soil on the growth of chard (Beta vulgaris), where they were treated with 5gm and 10gm for each pot separately, and mixing them with the same concentrations. The results showed a significant increase in germination rate and speed, germination stimulation index, plant height, number of branches, number of leaves, leaf weight ratio, fresh and dry weight, number of flowers, absolute growth rate, fertilizer efficiency. Potato peels and apples.